Spirituality and religion in patients with HIV/AIDS. - Cotton, Sian; Puchalski, Christina M; Sherman, Susan N; Mrus, Joseph M; Peterman, Amy H; Feinberg, Judith; Pargament, Kenneth I; Justice, Amy C; Leonard, Anthony C; Tsevat, Joel (Journal of general internal medicine, 2006)
Spirituality and religion are often central issues for patients dealing with chronic illness. The purpose of this study is to characterize spirituality/religion in a large and diverse sample of patients with HIV/AIDS by using several measures of spirituality/religion, to examine associations between spirituality/religion and a number of demographic, clinical, and psychosocial variables, and to assess changes in levels of spirituality over 12 to 18 months.
Keywords: Adaptation, Psychological; Adult; Alcohol Drinking; Ethnic Groups; Female; Follow-Up Studies; HIV Infections; Humans; Logistic Models; Male; Multivariate Analysis; Personal Satisfaction; Religion and Psychology; Residence Characteristics; Self Concept; Social Support; Spirituality; United States